KETERAMPILAN PROSES SAINS SISWA SMA PADA PEMBELAJARAN TERMOKIMIA MENGGUNAKAN MODEL INKUIRI TERBIMBING - Ratnasari, - (2015)
Keterampilan Proses Sains (KPS) dianggapsebagaiketerampilandasardanpentingbagisiswa, sehinggaperludiukurdalampembelajaran.TujuandaripenelitianiniadalahmemperolehinformasitentangpencapaianKPSsiswapadapembelajarantermokimiamenggunakan model inkuiriterbimbing.Metodepenelitian yang digunakanadalahpre-experimental, dengandesainpenelitianOne-shot Case Study.Subjekpenelitianadalahsiswapadasalahsatu SMA di Kota Bandung sebanyak 32 orang.Instrumenpenelitianberupatestertulis (pos-test), lembarobservasi, danpedomanwawancara.Hasilpenelitianmenunjukkanbahwaterdapatsembilanindikator KPS yang dikembangkan, meliputisatuindikator KPS yang tergolongsangatbaikyaitumengamati, dandelapanindikator KPS lainnyatergolongbaikyaitumengajukanpertanyaan, berhipotesis, merencanakanpercobaan, menggunakanalat/bahan, mengelompokkan, menerapkankonsep, menafsirkanpengamatan, danberkomunikasi. Pencapaianindikator KPS untuksiswakelompoktinggitergolongsangatbaik, sedangkanpadasiswakelompoksedangdanrendahtergolongbaik, meskipunsecarapersentase KPS siswakelompoksedanglebihtinggidibandingkansiswakelompokrendah.Secaraumum, pencapaian KPS seluruhsiswapadapembelajarantermokimiamenggunakan model inkuiriterbimbingtergolongbaik. Science Process Skills (KPS) is regarded as basic the skills and important for students, so that needs to be measured in learning. The purpose of this research is to obtain information of the KPS of students on learning thermochemistry using the guided inquiry. Research methodology that is pre-experimental, with the design research One-Shot Case Study. The subjects of study were students at senior high school in Bandung as many as 32 people. Research instruments of written tests (post-test), sheets of observation, and guidelines. The result of the research showed that there are nine indicators of KPS that were measured, that is an indicators of KPS could be categorized as very good that is observing, and the other eight indicators of KPS that belongs to good that is asking questions, making hypothesize, planing experiments, using tools/materials, classifying, applying concepts, interpreting observation, and communicating. The achievement indicators of KPS for the high group of students is very good, while middle and the low group of students belongs to good, even though the percentage KPS of the middle groups of students is higher than the low groups of students. Overall, KPS achievement of all students in learning thermochemistry used the guided inquiry categorized good.